Arabidopsis thaliana Plants Overexpressing the Barley Nicotinamine Synthase1 (HvNAS1) Gene Show Tolerance to Iron Deficiency - Emre Aksoy; Amir Maqbool; Buasimuhan Abudureyimu (Turkish Journal of Agriculture: Food Science and Technology)
Iron (Fe) is an important trace mineral for plant development, and plants grown in Fe deficiency experience yield losses due to the leaf chlorosis. In addition to agronomic measures that can be taken to minimize these losses, new plant genotypes can be developed effectively through genetic engineering. While dicots such as Arabidopsis thaliana use a reduction-based strategy to uptake high amounts of iron from the rhizosphere, the chelation strategy has evolved in Gramineous plants including barley (Hordeum vulgare). In this study, barley NICOTIANAMINE SYNTHASE1 (HvNAS1) gene, which is responsible for the production of nicotianamine that can complex with iron, was cloned and expressed at a constitutive high level in Arabidopsis plants. The expression levels of Arabidopsis genes encoding for the proteins involved in iron uptake increased together with HvNAS1 in the T3 Arabidopsis plants. Moreover, the root lengths, root and stem fresh weights, ferric chelate reductase enzyme activities of the plants also increased in the transgenic Arabidopsis plants under Fe deficiency. In addition, significant increases in iron and zinc levels were determined in the roots and shoots of transgenic Arabidopsis plants. As a result, transgenic Arabidopsis plants overexpressing the barley HvNAS1 gene can take up more iron from the rhizosphere and carry this iron to the shoots. This study demonstrates the power of genetic engineering to develop Arabidopsis plants overexpressing the HvNAS1 gene and therefore tolerate iron deficiency.